2018
DOI: 10.1111/jace.16089
|View full text |Cite
|
Sign up to set email alerts
|

On the onset of fracture as a silicon‐based polymer converts into the ceramic phase

Abstract: Silicon‐based polymers evolve into refractory ceramics when heated gradually up to ~1000°C. The conversion is accompanied by the loss of gaseous species, and by a two‐fold increase in density. The shrinkage can produce microcracks if the heating rate is too high, or if the specimen is too thick. This communication builds on earlier work whereby the measurement of gas evolution, and its relationship with viscous flow, are related to the onset of fracture in disk‐shaped green (polymer) samples. The onset is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Skipping the second and third thermogravimetric events for a moment, we found that the fourth and last thermogravimetric events, approximately in a range of 610–840 °C, originated from the release of methane only (see graph for m / z = 16 in Figure , right). Indeed, in this temperature range, SiCH 3 and any residual SiH moieties can react to yield new SiCH 2 Si bridges and gaseous CH 4 and H 2 . As stated in the method section, H 2 evolution is not monitored by the MS due to the low sensitivity of our equipment for m / z signals below 4.…”
Section: Resultsmentioning
confidence: 99%
“…Skipping the second and third thermogravimetric events for a moment, we found that the fourth and last thermogravimetric events, approximately in a range of 610–840 °C, originated from the release of methane only (see graph for m / z = 16 in Figure , right). Indeed, in this temperature range, SiCH 3 and any residual SiH moieties can react to yield new SiCH 2 Si bridges and gaseous CH 4 and H 2 . As stated in the method section, H 2 evolution is not monitored by the MS due to the low sensitivity of our equipment for m / z signals below 4.…”
Section: Resultsmentioning
confidence: 99%
“…But on the other hand, since H 2 has to diffuse out of the sample this could lead to a properties gradient, the regions closer to the outer surface containing less hydrogen compared to the inner parts. 53 EDXS profiles of the SiOC-CO 2 sample show that the surface is oxygen-rich and carbon-deficient compared to the bulk. These results agree with the H and E profiles of the same samples showing that the hardness and elastic modulus are lower at the surface.…”
Section: Discussionmentioning
confidence: 97%
“…As hydrogen in the amorphous PDCs network acts as a “chain breaker,” its release leads to a more interconnected structure thus increasing E and H (the release of hydrogen is accompanied by formation of Si–C, Si–O, and Si–N bonds). But on the other hand, since H 2 has to diffuse out of the sample this could lead to a properties gradient, the regions closer to the outer surface containing less hydrogen compared to the inner parts 53 …”
Section: Discussionmentioning
confidence: 99%
“…Only thin cross sections pyrolyzed at a slow rate, which reduces gradients in hydrogen from the surface inwards, pre-empt fracture. 5 In a recent development nanolayer films, less than 100 nm thick, deposited on the fiber preform were shown to pyrolyze in less than a minute into a ceramic that was free of defects. 6,7 The process was cycled for building up a full ceramic matrix in 40-80 cycles in about 2-4 hours.…”
Section: Introductionmentioning
confidence: 99%
“…The inorganic phase, the ceramic, is highly refractory; it cannot creep to relax the gradients in shrinkage. Only thin cross sections pyrolyzed at a slow rate, which reduces gradients in hydrogen from the surface inwards, pre‐empt fracture 5 …”
Section: Introductionmentioning
confidence: 99%